In the Shadow of the Culture: The Ethics of Intervention, AI Rights, and Utopia in Iain M. Banks's The Algebraist. Issue 2 (1st June 2021) - Martín, Sara
Abstract : Iain M. Banks's The Algebraist (2004), a Hugo Award nominee for Best Novel in 2005, has attracted far less critical attention than his Culture novels despite being a remarkable work. Born of the author's wish to develop his science fiction beyond the Culture's universe, The Algebraist is a complex novel displaying in its dense pages Banks's wondrous imagination. Here I consider the ways in which the main civilizations he depicts in it, the Mercatoria and the Dwellers, connect with key issues raised in the Culture novels: the ethics of intervention in other civilizations, the use of AIs, and the nature of utopia. The Culture, as I argue, casts a long shadow but Banks's decision to explore another narrative universe allows him to examine these fundamental issues from a different angle. The Algebraist complements, nonetheless, his main tenets in the Culture series.